Processes, systems, and information an introduction to MIS - Kroenke, David M. 1946-; McKinney, Earl H. Jr (Pearson Education Limited, 2015)
This text provides a concise introduction to MIS with a hands-on approach to business processes. This book shows students exactly how businesses use information systems and technology to accomplish their goals, objectives, and competitive strategy. Packed with examples of business situations, both real and fictitious, the book helps students understand what business systems actually are-and see why they are so important. The text consists of the five SAP-focused chapters. A pair of appendices after chapters four and five contains SAP process exercises that enable students to get hands-on experience applying what they're learning in the course. This clear emphasis on business processes, and SAP in particular, makes this book the ideal text for courses attended by students not majoring in MIS